2017
DOI: 10.1002/ams2.275
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrest caused by sibutramine obtained over the Internet: a case of a young woman without pre‐existing cardiovascular disease successfully resuscitated using extracorporeal membrane oxygenation

Abstract: CaseSibutramine is a weight loss agent that was withdrawn from the market in the USA and European Union because it increases adverse events in patients with cardiovascular diseases. However, non‐prescription weight loss pills containing sibutramine can be still easily purchased over the Internet.A 21‐year‐old woman without history of cardiovascular diseases developed cardiac arrest. She was a user of a weight loss pills, containing sibutramine and hypokalemia‐inducing agents, imported from Thailand over the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Use of monoamine oxidase inhibitors (MAOIs) and sibutramine can lead to increase of blood pressure [122,123]. The unintentional intake of compound like sibutramine because of contaminated DS could affect overall health, the intake of medicines which are used for management of serious diseases, and a professional sport career [124][125][126].…”
Section: Stanozololmentioning
confidence: 99%
“…Use of monoamine oxidase inhibitors (MAOIs) and sibutramine can lead to increase of blood pressure [122,123]. The unintentional intake of compound like sibutramine because of contaminated DS could affect overall health, the intake of medicines which are used for management of serious diseases, and a professional sport career [124][125][126].…”
Section: Stanozololmentioning
confidence: 99%
“…With this respect, other studies reported the presence of sibutramine, synephrine, oxilofrine, 1,4‐dimethylamylamine, deterenol, among others 10,22,24,58,59 . Most of these substances are prohibited in many countries and may cause severe side effects, like tremors, concentration deficiency, anxiety, high blood pressure, hyperthermia, heart failure, and stroke 60,61 . In addition, although we tried to replicate the PWS consumers' purchasing habits, a limited amount of samples was collected from different sources; thus, this may not be generalizable to all PWS present in Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…10,22,24,58,59 Most of these substances are prohibited in many countries and may cause severe side effects, like tremors, concentration deficiency, anxiety, high blood pressure, hyperthermia, heart failure, and stroke. 60,61 we suggest that future studies analyze the caffeine concentration of different lots over a period of time to assess inter-lot variation.…”
Section: Caffeine Daily Intake Assessmentmentioning
confidence: 99%
“…However, the continued presence of sibutramine in some over-the-counter weight loss formulations is a very concerning public health issue. The FDA has now implemented stricter guidelines for the control of dietary supplements, which is a welcome step to ensure public safety [ 10 ]. Aggressive internet-based marketing plays a vital role in capturing customers for over-the-counter supplements; unfortunately, despite its withdrawal from the market since 2010, sibutramine continues to be present in many antiobesity food supplements sold on the Internet [ 11 ].…”
Section: Discussionmentioning
confidence: 99%